2018
DOI: 10.1016/j.ijsu.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Firearm legislation, gun violence, and mortality in children and young adults: A retrospective cohort study of 27,566 children in the USA

Abstract: Firearm-related injuries types in hospitalized children are associated with age, race, and state level legislation. Accidents are most prevalent in young children, Whites, and states with lenient gun laws, while suicide attempts are more common in adolescents, Whites, and states with lenient gun laws. Suicide attempts are also associated with the greatest odds of in-hospital mortality. To address firearm violence, consideration should be given to legislation that promote safe gun storage behaviors and restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
2
20
2
1
Order By: Relevance
“…34,35 Pediatric firearm-related injuries are lower in the Northeast compared with other US regions and stricter gun laws in a region are associated with lower rates of pediatric firearm-related injuries. [61][62][63] Understanding these geographic trends and the factors underlying them may be useful in tailoring interventions aimed at reducing firearm injuries among children and teenagers.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Pediatric firearm-related injuries are lower in the Northeast compared with other US regions and stricter gun laws in a region are associated with lower rates of pediatric firearm-related injuries. [61][62][63] Understanding these geographic trends and the factors underlying them may be useful in tailoring interventions aimed at reducing firearm injuries among children and teenagers.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research, although not focused on NPW, has suggested that gun control laws can influence injuries among children. Accidental firearm injuries among children are higher in states with Stand-Your-Ground laws [20] and states with lenient gun laws had more firearm-related injuries including accidental injuries and suicide attempts [21,22]. Prior work has shown a link between regions of the U.S. with traditionally lenient gun laws and pediatric suicides by firearm.…”
Section: Current Legislation Surrounding Nonpowder Weapons and Child mentioning
confidence: 99%
“…Firearm-related injury is one of the top three causes of pediatric deaths in the U.S (Dowd & Sege, 2012; National Center for Injury Prevention and Control, 2018), and the country’s youth mortality rate due to firearms is the highest in the world (Centers for Disease Control and Prevention, 1997; Grinshteyn & Hemenway, 2016). Although aggression with firearms remains a big problem, especially among older teens (Srinivasan et al, 2014; Teplin et al, 2014), most firearm-related hospitalizations and many deaths in children are not a result of assault or homicide (Srinivasan et al, 2014; Kalesan et al, 2016a; Kalesan et al, 2016b; Monuteaux et al, 2016; Tseng et al, 2018). Several national studies have found that over three-fifths of hospitalizations due to firearms in children < 16 years of age were not assault-related (Kalesan et al, 2016b; Tseng et al, 2018; Hamilton et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Unintentional shootings are a significant cause of firearm-related injuries in children (Srinivasan et al, 2014; Kalesan et al, 2016a; Monuteaux et al, 2016). The majority of firearm-related hospital admissions for youth less than 15 years of age are due to unintentional injuries (Tseng et al, 2018; Hamilton et al, 2018a; Herrin et al, 2018). Approximately one-third of homes in the U.S. with children have one or more firearms (Johnson et al, 2004; Schuster et al, 2000; Hamilton et al, 2018b; Azrael et al, 2018), and they are frequently left loaded and unlocked where they are accessible to children (Schuster et al, 2000; Stennies et al, 1999).…”
Section: Introductionmentioning
confidence: 99%